Idiographic style features in drama (a case study: "American dream" by Edward Albee) - Bukach, Olga Vladislavovna; Shelestova, Olga Vadimovna (Филология: научные исследования, 2025)
The paper analyses peculiar features of Edward Albee's individual style with a special focus on drama being a synthetic art form, as well as the development of the theater of the absurd. The subject of the research is the ways of expressing the author's style in the text of the play "The American Dream"; the aim of the analysis is to identify the features of the expressive language that play a decisive role in conveying the intended meanings and ensuring the intended emotional impact on the recipient. The research methods include stylistic and linguo-cultural interpretation of the text, quantitative analysis, frequency analysis, as well as a method of continuous sampling. The methodology of idiostyle analysis suggests the use of cultural and anthropocentric approaches at the initial stage, as well as conducting linguistic analysis at the subsequent stage of the research. The research methodology involves using cultural and anthropocentric approaches to analyze historical context, the speech characteristics of characters, and the emotional impact on the reader (and the viewer); the linguistic analysis allowed to identify the idiographic features of the author's style in lines the characters have. These features are: anaphora, epiphora, and polysyndeton, as well as numerous lexical repetitions. The said repetitions of different types allow the author to achieve a sense of detachment typical for theatre of absurd works. This technique creates a picture of an indifferent and cruel society, where communication is devoid of meaning and people are not interested in connecting with each other; moreover, the repetitions provide a certain rhythmic organization of dialogues and, therefore, create the dynamics each scene demands. The results can be used when working with existing translations or when creating new translations of this play and other works by this author with the aim of accurately reflecting the features of the author's style in the translated texts. This approach appears to be particularly relevant because, during his lifetime, the renowned playwright closely monitored the interpretations of his plays, sometimes forbidding the productions from being staged; after 2016, his foundation adheres to a similar policy. The method of analysis proposed in the article will allow to achieve the precise transmission of the author's intention in translated texts, further granting directors and actors an opportunity to achieve the necessary emotional impact on the audience.